Primary-aged children’s participation activities that influence adult decision-making: a scoping literature review - Melanie Macer (Educational Futures)
Children’s participation lies at the intersection of children’s rights and the ‘new’ sociology of childhood. Informed by these frameworks, this scoping literature review identified seven empirical studies involving primary-aged children’s participation in adult decision-making; employing the search string: (child* OR pupil) AND primary AND (empower* OR participat* OR consult* OR involve* OR influenc* OR decision*). This review describes a range of characteristics associated with these children’s participatory activities, embedded within consultations, pupil voice circle meetings, participatory action research projects, pupil councils and membership of a strategic board. The type of adult decisions being influenced included issues relating to school domestics, teaching and learning, the local community and local government. This review offers guidance to those aiming to develop children’s participation in adult decision-making by illuminating factors that can support this process.